2002
DOI: 10.1128/jcm.40.2.490-494.2002
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Quantitative, Touch-Down, Real-Time PCR Assay for Diagnosing Pneumocystis carinii Pneumonia

Abstract: A rapid (time to completion, <4 h, including DNA extraction) and quantitative touch-down (QTD) real-time diagnostic Pneumocystis carinii PCR assay with an associated internal control was developed, using fluorescence resonance energy transfer (FRET) probes for detection. The touch-down procedure significantly increased the sensitivity of the assay compared to a non-touch-down procedure. Tenfold serial dilutions of a cloned target were used as standards for quantification. P. carinii DNA has been detected in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
141
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(150 citation statements)
references
References 39 publications
(8 reference statements)
3
141
1
4
Order By: Relevance
“…PCP has nonspecific clinical symptoms such as dyspnea, fever and nonproductive cough that are similar to many infectious agents. Although a variety of polymerase chain reaction (PCR) methods, such as nested-PCR and real-time PCR, have been developed for the diagnosis of PCP, these assays are not conventional in most clinical microbiology laboratories and are not easily available, especially in developing countries (Bandt and Monecke 2007;Contini et al 1998;Larsen et al 2002). Therefore, the standard laboratory method for diagnosis of PCP is microscopic examination of the clinical specimen such as induced sputum, bronchoalveolar lavage (BAL) and lung biopsy after some types of staining methods (Takahashi et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…PCP has nonspecific clinical symptoms such as dyspnea, fever and nonproductive cough that are similar to many infectious agents. Although a variety of polymerase chain reaction (PCR) methods, such as nested-PCR and real-time PCR, have been developed for the diagnosis of PCP, these assays are not conventional in most clinical microbiology laboratories and are not easily available, especially in developing countries (Bandt and Monecke 2007;Contini et al 1998;Larsen et al 2002). Therefore, the standard laboratory method for diagnosis of PCP is microscopic examination of the clinical specimen such as induced sputum, bronchoalveolar lavage (BAL) and lung biopsy after some types of staining methods (Takahashi et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a quantitative real-time PCR assay that targeted Pneumocystis Major Surface Glycoprotein (MSG) multigene family was applied to OW samples, and revealed significant differences between PcP patients and Pneumocystis colonized subjects in the number of MSG copies. The authors suggested a cutoff value of 50 MSG gene fragment copies/tube for distinguishing between the two conditions (Larsen et al, 2002). However, quantitative PCR results seemed difficult to use on the field.…”
Section: Molecular Detection Of Pneumocystismentioning
confidence: 99%
“…In common practice, this difficulty is often solved on the basis of a careful clinical, radiological and laboratory assessment of the patient pathological condition, as it is usually done to other infectious diseases, especially when their agents are opportunistic pathogens. However, the alternative of quantifying parasite rates was also explored (Larsen et al, 2002). Thus, a quantitative real-time PCR assay that targeted Pneumocystis Major Surface Glycoprotein (MSG) multigene family was applied to OW samples, and revealed significant differences between PcP patients and Pneumocystis colonized subjects in the number of MSG copies.…”
Section: Molecular Detection Of Pneumocystismentioning
confidence: 99%
“…It is thought that real-time PCR, as recently described [5,14], might be useful in distinguishing between colonization and clinical disease. This sugges-tion is based on the hypothesis that PCP patients should have a higher organism burden than colonized or subclinically infected patients, and that this would be reflected by a higher amount of Pneumocystis jiroveci DNA present in the extracted specimens from PCP patients.…”
Section: Pneumocystis Jiroveci Formerly Known Asmentioning
confidence: 99%
“…Standards and external controls: To obtain standards for real-time PCR, P. jiroveci-positive BAL samples (by Grocott smear) were used. The extracted DNA (described above in Preparation of DNA specimens) was used for amplification of the major surface glycoprotein (MSG) gene of Pneumocystis [14]. A PCR method previously described [11] was modified for the real-time assay.…”
Section: Conventional Pcrmentioning
confidence: 99%